2017
DOI: 10.1002/er.3828
|View full text |Cite
|
Sign up to set email alerts
|

Transient analysis for liquid-fuel molten salt reactor based on MOREL2.0 code

Abstract: SummaryA molten salt reactor (MSR) is characterized by simultaneously using liquid fuel salt as both the nuclear fuel and coolant. The redistribution of delayed neutron precursors (DNPs) makes the transient behavior of MSRs different from traditional solid-fuel reactors. In this study, a 3D coupled neutronics/thermal hydraulics code, MOREL2.0, was employed to analyze a liquid-fuel Thorium Molten Salt Reactor (TMSR-LF) under perturbations of fuel pump start-up and coast-down and by overheating and overcooling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Other efforts have also completed safety assessments using methodologies published from IAEA's International Project on Innovative Nuclear Power Reactor and Fuel Cycles (INPRO) [30]. Published safety analyses of MSRs using an assortment of nuclear codes, often coupled with thermal hydraulic codes, are available in refs [31][32][33][34][35][36][37][38][39]. Some of these efforts have shown that source term functionality can be added to these codes by tracking specific fission product isotopes with the flow [40][41][42][43].…”
Section: Molten Salt Reactorsmentioning
confidence: 99%
“…Other efforts have also completed safety assessments using methodologies published from IAEA's International Project on Innovative Nuclear Power Reactor and Fuel Cycles (INPRO) [30]. Published safety analyses of MSRs using an assortment of nuclear codes, often coupled with thermal hydraulic codes, are available in refs [31][32][33][34][35][36][37][38][39]. Some of these efforts have shown that source term functionality can be added to these codes by tracking specific fission product isotopes with the flow [40][41][42][43].…”
Section: Molten Salt Reactorsmentioning
confidence: 99%
“…The code is validated with MSRE data, proves to be of similar accuracy as the previous version, and has increased speedups for both steady-state and transient scenarios by considerable amounts. They later modeled the power and temperature as a function of time for scenarios such as a pump driven transient, an unprotected fuel pump startup and coast-down at zero and normal power, an inlet fuel temperature driven transient, and overheating and overcooling of inlet fuel [141]. This work shows the importance of system modeling for source term modeling, as time and space dependent temperature modeling during transient scenarios has a very important and direct impact on radionuclide speciation, transport, and many other phenomena that affect its evolution during a severe accident.…”
Section: Salt-fueled Molten Salt Reactorsmentioning
confidence: 99%